Pengembagan Perangkat Pembelajaran Team Based Learning- Inquiry Pada Pembelajaran Daring Berbantuan WhatsApp Dan Zoom Meeting Pada Materi Gerak Lurus - Trisnawaty J. Buhungo; Darmansya A Mustapa; Asri Arbie (Department of Physics Education, Universitas Mataram, 2021)
This research was conducted at SMAN 1 Telaga Biru class X MIPA3. The purpose of this study is to produce quality learning tools using the Team Based Learning model to improve student learning outcomes in physics learning. This research uses a modified development model of the ten steps of Borg and Gall's research and development by Sukmadinata and colleagues which consists of three stages, namely preliminary studies, product development, and product testing and dissemination of results. The results showed that: 1) The overall validation of the learning tools was declared valid with a small revision, 2) The practicality of the learning devices was determined through the average percentage of learning implementation in four meetings reaching 97.22% with very good criteria and teacher and student responses through questionnaires. give a positive response. Based on the results of the study, it can be concluded that the Physics learning device using the Team Based Learning model has met the valid and practical criteria to increase student interest in learning and learning outcomes.